HADRAH SEBAGAI MEDIA DAKWAH DALAM MENINGKATKAT AKTIVITAS KEAGAMAAN DI PONDOK PESANTREN - Berlian, Putri (JURNAL SAHID DA'WATII, 2022)
Hadrah as a Da'wah Media in Increasing Religious Activities at the Nurul Ibad Islamic Boarding School. This study aims to determine the effect of hadrah as a medium of da'wah in increasing religious activity at the Nurul Ibad Islamic Boarding School, Ciampea sub-district, Bogor Regency. This study uses a quantitative approach method with data collection techniques using a statement questionnaire with 4 alternative answers. There are two variables, namely variable (X) hadrah as a medium of da'wah and variable (Y) religious activity. The population used in this study were Nurul Ibad students with a sampling technique of 33 students, of which the Nurul Ibad students were hadrah performers at the Nurul Ibad Islamic Boarding School. Data were analyzed using the linear regression formula, so that the tcount value was 5.120 < ttable 2.039, which means that hadrah as a medium of preaching had a significant effect on increasing religious activity at the Nurul Ibad Islamic Boarding School, Ciampea sub-district, Bogor regency.